Cryopreservation of lomandra sonderi (asparagaceae) shoot tips using droplet-vitrification - Menon, Akshay; Funnekotter, Bryn; Kaczmarczyk, Anja; Bunn, E.; Turner, S.; Mancera, Ricardo (CryoLetters C/- Royal Veterinary College, 2012)
A cryopreservation protocol was developed for Lomandra sonderi (Asparagaceae), an endemic plant of southwest Western Australia used for mine site restoration. Thermal analysis of L. sonderi shoot tips using differential scanning calorimetry was used to detect the formation of ice in shoot tips and consequently allowed optimisation of the time of incubation in plant vitrification solution 2 (PVS2), which attempted to minimise phytotoxicity of, and excessive dehydration by, its cryoprotective components. Sugar pretreatments did not improve survival. Use of a loading solution containing 2 M glycerol and 0.4 M sucrose prior to incubation in PVS2 improved survival of control shoot tips. Preconditioning at 20+/-1 degree C day/night alternating temperature with a 16 h photoperiod or at a constant 5 degree C temperature with a 12 h photoperiod both significantly improved both control shoot tip survival and post-cryopreservation survival. Shoot tips that recovered from liquid nitrogen immersion were successfully re-established as actively growing in vitro plantlets.